The problem of musculoskeletal pain: what is interesting for the practitioner? Data of a survey of 846 Russian physicians - A. E. Karateev (Современная ревматология)
The paper presents the results of a survey of 846 Russian physicians (neurologists, rheumatologists, orthopedic traumatologists, general practitioners, and therapists), whose work is associated with the treatment of musculoskeletal pain. The physicians have been asked to answer which topics they consider important for their education. It turns out that the first place is occupied by the issues of differential diagnosis of the most common musculoskeletal diseases and current methods for their treatment (interventional methods in particular), as well as the problems of rational use of nonsteroidal anti-inflammatory drugs. More than half of the respondents find it interesting to discuss the legal aspects of a physician's work.